Extracranial Vertebral Artery Aneurysm Associated with Neurofibromatosis Type 1: A Case Report - Hiramatsu, H. (Centauro S.r.l., 2007)
Extracranial vertebral artery aneurysm associated with neurofibromatosis (NF1) is very rare. The aneurysm was successfully treated by endovascular trapping of the aneurysm and proximal vertebral artery with coils.